2018
DOI: 10.1002/stco.201800021
|View full text |Cite
|
Sign up to set email alerts
|

Structural performance of CHS X‐joints fabricated from high‐strength steel

Abstract: Representative steel design standards have limited the use of high-strength steels to tubular joints, partly because of concerns about their unique material characteristics. However, the mechanical background behind the limitations is unclear, and its validity needs to be re-evaluated. In this study, a set of CHS (circular hollow section) X-joints fabricated from cold-formed tubes was tested under static axial compression. Then, as supplemental work, extensive test-validated numerical analyses were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Yan et al (2022a) found that neither C f nor the 0.8 f u restriction is necessary for designing HSS rectangular hollow section (RHS) X-joints in tension based on the experimental data presented in (Becque and Wilkinson, 2017; Björk and Saastamoinen, 2012; Feldmann et al, 2016; Tuominen and Björk, 2017; Yan et al, 2022a). The mechanical behaviour of joints beyond the experimental configuration is commonly studied using a verified finite element (FE) model (Björk and Saastamoinen, 2012; Huang et al, 2021; Kim et al, 2019; Lan et al, 2019, 2021; Lee and Kim, 2018; Lee et al, 2017; Liu et al, 2018; Ma et al, 2015; Mohan and Wilkinson, 2022; Tuominen and Björk, 2017; Xin et al, 2021). As the joints fail by a fracture in the heat-affected zone (HAZ) or in the base material (BM), it is essential to conduct an advanced numerical study considering both the stress-strain relationship of HAZ and the material damage model.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al (2022a) found that neither C f nor the 0.8 f u restriction is necessary for designing HSS rectangular hollow section (RHS) X-joints in tension based on the experimental data presented in (Becque and Wilkinson, 2017; Björk and Saastamoinen, 2012; Feldmann et al, 2016; Tuominen and Björk, 2017; Yan et al, 2022a). The mechanical behaviour of joints beyond the experimental configuration is commonly studied using a verified finite element (FE) model (Björk and Saastamoinen, 2012; Huang et al, 2021; Kim et al, 2019; Lan et al, 2019, 2021; Lee and Kim, 2018; Lee et al, 2017; Liu et al, 2018; Ma et al, 2015; Mohan and Wilkinson, 2022; Tuominen and Björk, 2017; Xin et al, 2021). As the joints fail by a fracture in the heat-affected zone (HAZ) or in the base material (BM), it is essential to conduct an advanced numerical study considering both the stress-strain relationship of HAZ and the material damage model.…”
Section: Introductionmentioning
confidence: 99%